Vaccination coverage in children under one year of age and associated socioeconomic factors: maps of spatial heterogeneity - Matheus Adriano Divino Pereira; Luis Henrique Arroyo; Maria Del Pilar Serrano Gallardo; Ricardo Alexandre Arcêncio; Josianne Dias Gusmão; Gabriela Gonçalves Amaral; Valéria Conceição de Oliveira; Eliete Albano de Azevedo Guimarães (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to analyze vaccination coverage spatial distribution in children under one year old and the socioeconomic factors associated with meeting the recommended goals in Minas Gerais. Methods: an ecological study, carried out in 853 municipalities in the state. Pentavalent, poliomyelitis, meningococcal conjugate, yellow fever, rotavirus, and 10-valent pneumococcal conjugate vaccination coverage were analyzed. Scan statistics and multiple logistic regression were performed to identify spatial clusters and factors associated with meeting coverage goals. Results: spatial analysis revealed clusters with risk of low coverage for all vaccines. Number of families with per capita income of up to 1/2 wage, Minas Gerais Social Responsibility Index and percentage of the poor or extremely poor population were associated with meeting the established goals. Conclusions: the results are useful for designing interventions regarding the structuring of vaccination services and the implementation of actions to increase vaccination coverage in clusters with less propensity to vaccinate.